The Movement of Muhammadiyah Women: Religious Values, Culture, and Gender Equality - Rahmaniah, Aniek; Susanti, Emy; Budi Hendrarti, Dwi Windyastuti; Sari, Ulfi Andrian (Jurnal Ilmiah Peuradeun, 2025)
This study analyzed and explored social practices and community-based movements for gender justice carried out by the females of Muhammadiyah. To this point, there has been a duality in supporting the epistemological construction, which is the status of women and their role in the public sphere. This study employed a qualitative interpretive approach with an ethnomethodology approach by conducting observations, conducting interviews, and being involved in social dynamics activities and community-based education. This study was conducted in Malang City, with the consideration that there are social dynamics and community-based movements carried out by Muhammadiyah’s females for gender justice. Informants in the research were Muhammadiyah Regional Leaders, Aisyiyah Regional Leaders, Nasyiatul Aisyiyah Regional Leaders, active members of Muhammadiyah, and Muhammadiyah mothers who were involved in social activities with gender ideology. The data were analyzed by inductive data analysis. This study found out that the social dynamics and community-based education movement for gender justice carried out by Muhammadiyah’s females are as follows: (1) religious activities, disseminating the amr ma’ruf nahi munkar movement and Islamic egalitarianism; (2) education and advocacy on women’s issues (local dynamics); (3) agency, which was divided into mainstream groups (conservative-literal, rational-praxis), and religion’s critical-reinterpretation group for gender justice.